Elderly training for prevention of home falls using information and communication technologies - Campos, Karis de; Santos, Mariana Alves dos; Barros, Nicolli Macedo; Simionato, Thaís Marques; Brandão, Jayse Gimenez Pereira; Ramos, Ana Paula Mansano Cunha (Journal of Health Care, 2017)
Introduction: Falls are considered a public health problem due to their high morbidity and mortality, being one of the main causes of accidental death in individuals over 65 years. They also entail loss of capacity among the elderly, reducing their quality of life. Objectives: To elaborate for the elderly a training program on home falls using Information and Communication Technologies (ICTs), subsequently disseminating the acquired knowledge to their peers; and to evaluate the effectiveness of the training program. Methodology: The study was developed by five students of the Academic League of Geriatrics of the Faculty of Medicine of the University of Mogi das Cruzes with the University Open to Integration (Unai) in Mogi das Cruzes (SP), Brazil. Eleven Unai students of both sexes, aged 60 and over, participated voluntarily of this study. The activities were divided into five stages using ICTs in addition to the application of a pre and a post-qualification questionnaire on the subject. The results were analyzed qualitatively and in a descriptive statistics way. Results: Elderly people had a good prior knowledge of falls related subjects. Most of the questions were known, and the high pre and post-qualification hit rate was maintained. The transmitted content was exposed by the participants to the other Unai academics through lectures and theater. Conclusion: There was acceptance and interest of the elderly regarding the technologies used during the training and the presentation to their peers, which contributed to the increase in knowledge about home falls, verified in the post-qualification questionnaire.